2008
DOI: 10.1159/000151396
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Adiponectin and Adiponectin Receptors in Human Pituitary Gland and Brain

Abstract: Background/Aims: Adiponectin and its receptors, AdipoR1 and AdipoR2, constitute integral components of energy homeostatic mechanism in peripheral tissues. Recent studies have implicated adiponectin in central neural networks regulating food intake and energy expenditure. The present study aimed at investigating the possible expression and distribution of adiponectin and its receptors in human pituitary gland, hypothalamus and different brain areas. Methods: Sections of the pituitary gland, hypothalamus and adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
108
1
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 86 publications
2
108
1
9
Order By: Relevance
“…All analyses were standardized to the minor allele ADIPOQ locus and eating behavior Beside its well-described role in endocrine metabolism and cardiovascular function in peripheral tissues as well as the reported autocrine effects on adipocytes (Wu et al 2003), adiponectin confers also central effects on energy expenditure or food intake (Kubota et al 2007;Qi et al 2004;Kadowaki et al 2008). It was recently shown that adiponectin is also expressed in brain (Rodriguez-Pacheco et al 2007;Psilopanagioti et al 2009) and is functionally active (Rodriguez-Pacheco et al 2007). In addition, several studies reported intracerebral injection (Hoyda et al 2009a;Iwama et al 2009;Park et al 2011) and most importantly expression of adiponectin receptors in the brain (Hoyda et al 2009b;Dadson et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were standardized to the minor allele ADIPOQ locus and eating behavior Beside its well-described role in endocrine metabolism and cardiovascular function in peripheral tissues as well as the reported autocrine effects on adipocytes (Wu et al 2003), adiponectin confers also central effects on energy expenditure or food intake (Kubota et al 2007;Qi et al 2004;Kadowaki et al 2008). It was recently shown that adiponectin is also expressed in brain (Rodriguez-Pacheco et al 2007;Psilopanagioti et al 2009) and is functionally active (Rodriguez-Pacheco et al 2007). In addition, several studies reported intracerebral injection (Hoyda et al 2009a;Iwama et al 2009;Park et al 2011) and most importantly expression of adiponectin receptors in the brain (Hoyda et al 2009b;Dadson et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Lately it has been shown to be of importance to categorize the visual food stimuli in low versus high calorie stimuli as this could influence the results especially during the fasting state [47]. Also, recently published data have implicated adiponectin in regulating food intake and energy expenditure [48,49]. Moreover, glucagon-like peptide-1 (GLP-1), which is synthesized in the brain as well [50,51], may also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of AdipoR1 and AdipoR2 was observed in hippocampal neurons in mice, GT1-7 cell line derived from mouse hypothalamic neurons in rat, and the pituitary, nucleus basalis and hypothalamus in humans (Jeon et al 2009;Wen et al 2008;Guillod-Maximin et al 2009;Psilopanagioti et al 2009). Adiponectin-knockout mice exhibit enlarged brain infarction and increased neurological deficits after ischemia reperfusion compared to wild-type mice, while adenovirus-mediated supplementation of adiponectin significantly reduces cerebral infarct size in both wild-type and adiponectin-deficient mice (Nishimura et al 2008), suggesting that adiponectin may have neuroprotective activity.…”
Section: Introductionmentioning
confidence: 98%